2009
DOI: 10.1038/nature08025
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding protein KSRP promotes the biogenesis of a subset of microRNAs

Abstract: Consistent with the role of microRNAs (miRNAs) in down-regulating gene expression by reducing translation and/or stability of target mRNAs1, the levels of specific miRNAs are important for correct embryonic development and have been linked to several forms of cancer2-4. However, the regulatory mechanisms by which primary miRNAs (pri-miRNAs) are processed first to precursor miRNAs (pre-miRNAs) and then to mature miRNAs by the multiprotein Drosha and Dicer complexes5-8, respectively, remain largely unknown. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
574
6
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 605 publications
(601 citation statements)
references
References 40 publications
19
574
6
2
Order By: Relevance
“…Lin28 is known to block the production of a group of microRNAs, including let-7 microRNAs, which have been implicated previously in the regulation of cell proliferation and differentiation (Bussing et al, 2008;Heo et al, 2009;Trabucchi et al, 2009). The observed growth inhibition following Lin28 repression is likely the result, at least in part, of a restoration in let-7 microRNA expression, which has been linked to a translational blockade of target mRNAs involved in promoting cell cycle progression (Bussing et al, 2008).…”
Section: Sub-population Of Eoc Cells Co-expresses Lin28 and Oct4mentioning
confidence: 99%
See 1 more Smart Citation
“…Lin28 is known to block the production of a group of microRNAs, including let-7 microRNAs, which have been implicated previously in the regulation of cell proliferation and differentiation (Bussing et al, 2008;Heo et al, 2009;Trabucchi et al, 2009). The observed growth inhibition following Lin28 repression is likely the result, at least in part, of a restoration in let-7 microRNA expression, which has been linked to a translational blockade of target mRNAs involved in promoting cell cycle progression (Bussing et al, 2008).…”
Section: Sub-population Of Eoc Cells Co-expresses Lin28 and Oct4mentioning
confidence: 99%
“…It has been shown to block the processing of let-7 microRNAs (Heo et al, 2008;Newman et al, 2008;Rybak et al, 2008;Viswanathan et al, 2008) as well as a handful of other microRNAs (Heo et al, 2009;Trabucchi et al, 2009). In addition, Lin28 has been reported by us and others to bind to a specific subset of mRNAs, including those for IGF-2, Oct4, and several cell cycle-related factors, thereby modulating their translation (Polesskaya et al, 2007;Qiu et al, 2009;.…”
Section: Introductionmentioning
confidence: 99%
“…KSRP/FUBP2 is implicated in a variety of cellular processes, including splicing in the nucleus, mRNA decay, maturation of miRNA, and transcriptional control of proto-oncogenes such as c-myc. [13][14][15][16] The domain structure of KSRP/FUBP2 consists of a PG-rich amino-terminus, four KH-type nucleic acid-binding domains, and a Q-rich carboxy (C)-terminus ( Figure 4A). 17 To identify the GO-Y086-binding site on KSRP/FUBP2, pull down assays were carried out using different GFP-tagged deletion mutants of KSRP/FUBP2 ( Figure 4B).…”
mentioning
confidence: 99%
“…Our findings strongly support the latter model, and suggest that further analyses are required to precisely dissect the role of the pri-miRNA loop in miRNA processing in vivo. Although several regulatory proteins have been demonstrated to bind to pri/pre-miRNA loops and affect the production of mature miRNA (Heo et al, 2008;2009;Michlewski and Caceres, 2010;Newman et al, 2008;Trabucchi et al, 2009;Viswanathan et al, 2008) and conserved loop sequences are required for the interaction between these regulatory factors (Heo et al, 2009;Newman et al, 2008), none of these proteins have been shown to be involved in the regulation of the processing accuracy of the mature miRNA 5′ seed region. Additionally, 5′ end polymorphisms have been detected in miRNA profiles of CD8 T cells (Wu et al, 2007), but there is little evidence to explain the heterogeneity of the 5′ end of mature miRNAs.…”
Section: Discussionmentioning
confidence: 99%